Data on New Intermediate and Accidental Hosts Naturally Infected with Angiostrongylus cantonensis in La Gomera and Gran Canaria (Canary Islands, Spain) - Natalia Martin-Carrillo; Edgar Baz-González; Katherine García-Livia; Virginia Amaro-Ramos; Néstor Abreu-Acosta; Jordi Miquel; Estefanía Abreu-Yanes; Román Pino-Vera; Carlos Feliu; Pilar Foronda (Animals, 2023)
Angiostrongylus cantonensis is a metastrongyloid nematode and the etiologic agent of angiostrongyliasis, a disease characterized by eosinophilic meningitis. This emerging zoonotic parasite has undergone great expansion, including in some regions of Europe and America. In the Canary Islands, the parasite was first discovered parasitizing Rattus rattus on the island of Tenerife in 2010. To date, the distribution of this parasite in the Canary Islands has been restricted to the northern zone and the main cities of Tenerife. Using molecular tools for the sentinel species present in the Canary Islands, this study confirmed the presence of the nematode on two other islands in the Canary Archipelago: La Gomera and Gran Canaria. Furthermore, this emerging parasite was detected, besides in the common definitive host R. rattus, in wild Mus musculus and Felis catus and in four terrestrial gastropod species, Limacus flavus, Milax gagates, Insulivitrina emmersoni, and Insulivitrina oromii, two of them endemic to La Gomera, for the first time, increasing the number of non-definitive host species. This study reinforces the expansion character of A. cantonensis and highlights the importance of knowledge about sentinel species for identifying new transmission locations that help prevent and control the transmission of the parasite and, thus, prevent public health problems.